Mathematics Communication Skill Analysis Seen from Emotional Quotient on Fast Feedback in Missouri Mathematics Project Learning - Swari, Ignasia Santi Kumala; Kartono, Kartono; Walid, Walid (Universitas Negeri Semarang, 2021)
This research aimed to find out mathematics communicaiton skill pattern of students seen from emotional quotient on Missouri Mathematics Project learning with fast feedback. This mix method research used sequential explanatory design. The population consisted of VIII graders of SMP N 1 Kedung Tahunan in academic year 2018/2019. The subjects were from VIII C of the school. The findings showed that mathematics communicaiton skill seen from emotional quotient was varied. As for example, students with sensitivity type emotional quotient consisted of 4 high categorized students, 11 moderate students, and 1 poor level student. The competency typed students consisted of 1 high category student, 10 moderate, and 1 with poor level.